2017
DOI: 10.1038/srep46562
|View full text |Cite
|
Sign up to set email alerts
|

Novel interactions of the von Hippel-Lindau (pVHL) tumor suppressor with the CDKN1 family of cell cycle inhibitors

Abstract: Germline inactivation of the von Hippel-Lindau (VHL) tumor suppressor predisposes patients to develop different highly vascularized cancers. pVHL targets the hypoxia-inducible transcription factor (HIF-1α) for degradation, modulating the activation of various genes involved in hypoxia response. Hypoxia plays a relevant role in regulating cell cycle progression, inducing growth arrest in cells exposed to prolonged oxygen deprivation. However, the exact molecular details driving this transition are far from unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 77 publications
(101 reference statements)
3
11
0
Order By: Relevance
“…As the number of acidic repeats forming pVHL30 N-terminal tail increases from rodents to primates 22 , data suggest that the isoform-dependent MDM2/pVHL30 association could have specifically evolved in higher mammals. We further observed that the cluster of positive charges in region 329-351 appears counterbalanced by an opposed concentration of negative charges in region 410-433 (Figure S12), supporting the hypothesis that the two flanking sequences interact with the pVHL30 acidic N-terminus and β-domain, respectively, as pVHL β-domain presents a number of conserved positive residues mediating multiple protein-protein interactions 10,33,28 . Notably, MDM2 residues spanning 351-433 fragment includes six ATM (ataxia-telangiectasia mutated kinase) phosphorylation sites (i.e., S386, S395, S407, T419 S425, S429, Figure S12), strongly suggesting that post-translational modifications may operate as regulator of MDM2/pVHL30 association, e.g.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As the number of acidic repeats forming pVHL30 N-terminal tail increases from rodents to primates 22 , data suggest that the isoform-dependent MDM2/pVHL30 association could have specifically evolved in higher mammals. We further observed that the cluster of positive charges in region 329-351 appears counterbalanced by an opposed concentration of negative charges in region 410-433 (Figure S12), supporting the hypothesis that the two flanking sequences interact with the pVHL30 acidic N-terminus and β-domain, respectively, as pVHL β-domain presents a number of conserved positive residues mediating multiple protein-protein interactions 10,33,28 . Notably, MDM2 residues spanning 351-433 fragment includes six ATM (ataxia-telangiectasia mutated kinase) phosphorylation sites (i.e., S386, S395, S407, T419 S425, S429, Figure S12), strongly suggesting that post-translational modifications may operate as regulator of MDM2/pVHL30 association, e.g.…”
Section: Resultssupporting
confidence: 73%
“…Functional intersections between oxygen sensing, apoptosis and cell cycle regulation are well described in the literature 26,28,44,45 , although their functional inter-connection and mutual regulation are still debated. In particular, under prolonged hypoxia, p53 has been reported to accumulate in the cell, yielding a direct repression of HIF-1α transcriptional activity 46 .…”
Section: Discussionmentioning
confidence: 99%
“…As the number of acidic repeats forming pVHL30 N-terminal tail increases from rodents to primates 22 , data suggest that the isoform-dependent MDM2/pVHL30 association could have specifically evolved in higher mammals. We further observed that the cluster of positive charges in region 329-351 appears counterbalanced by an opposed concentration of negative charges in region 410-433 ( Figure S11), supporting the hypothesis that the two flanking sequences interact with the pVHL30 acidic N-terminus and β-domain, respectively, as pVHL β-domain presents a number of conserved positive residues mediating multiple protein-protein interactions 10,28,33 . Notably, MDM2 residues spanning 351-433 fragment includes six ATM (ataxia-telangiectasia mutated kinase) phosphorylation sites (i.e.…”
Section: Resultssupporting
confidence: 73%
“…Manually curated enrichment of protein-protein interactions across network nodes further extended the connection between clusters I and II. Considering the concept of "interactors of interactors", a well-established property of protein-protein interaction networks 28,29 and the already validated physical interaction between pVHL, p53, and p14ARF, our in silico analysis predicts that MDM2 is a novel direct interactor of pVHL.…”
Section: Resultsmentioning
confidence: 95%
“…Further, correlation between pVHL and kinase activity is not limited to the direct association with kinases. In a previous work, we reported the direct interaction between pVHL and the CDKN1 kinase inhibitor protein family [ 57 ]. We found that the CDKN1 proteins share a conserved region mimicking the HIF-1 α motif responsible for pVHL binding.…”
Section: Introductionmentioning
confidence: 99%